Toxic emissions resulting from sucralose added to electronic cigarette liquids. Issue 10 (3rd October 2019) - El-Hage, Rachel; El-Hellani, Ahmad; Haddad, Christina; Salman, Rola; Talih, Soha; Shihadeh, Alan; Eissenberg, Thomas; Aoun Saliba, Najat
Abstract: Electronic cigarettes (ECIGs) are appealing in part because of the many flavors of the liquids used in them. Concerns have been raised that some ECIG liquid flavors, especially those that are sweet, are attracting otherwise nicotine-naïve youth to ECIGs. Sucralose is an artificial, non-caloric sweetener that is added to some ECIG liquids. In this study, we evaluated the toxicants, namely isomers of chloropropanols that can be produced when sucralose-containing ECIG liquid is aerosolized. An analytical separation method relying on solid-phase extraction (SPE) to isolate chloropropanols from the propylene glycol/glycerol matrix was developed. Chloropropanols were then derivatized by silylation before they were analyzed on GC-MS. The influence of different ECIG operating conditions on the generation of chloropropanols was studied by varying ECIG device design and power output and also the sucralose concentration of the liquid. Heated sucralose-containing ECIG liquids produce two toxic compounds that can be found in the resulting aerosols. The two chloropropanols, 3-monochloro-1, 2-propanediol (3-MCPD), and 1, 3-dichloropropanol (1, 3-DCP) that were detected under all conditions were found to be correlated significantly with liquid sucralose content. Effective regulation of ECIGs will minimize user and bystander exposure to these and other ECIG toxicants. Copyright © 2019 American Association for Aerosol Research